Suicide rates in rural Tamil Nadu, South India: verbal autopsy of 39 000 deaths in 1997-98. - Gajalakshmi, V; Peto, R; Peto, R (2007)
BACKGROUND: In India, death registration is not complete, especially in rural areas. Chiefly for other purposes special efforts were made to identify all deaths that occurred during 1997-98 in rural areas of one of the districts in Tamil Nadu, South India, and the verbal autopsy was done. METHODS: Trained non-medical field interviewers interviewed surviving spouses, close associates or neighbours, and wrote the verbal autopsy reports in the local language (Tamil). The reports were reviewed independently by two physicians to arrive at the probable underlying cause of death. About 5% of the data were randomly selected for re-interview. RESULTS: The verbal autopsy was done for 38 836 deaths. Injuries accounted for 18.5% of the total deaths. About half of these were suicides. The average annual suicide rate for men and women were 71 and 53/100 000, respectively. Three-fourths of all suicides were in the socially and economically productive age-group of 15-44 years. At ages 15-24 years the female suicide rate of 109/100 000 exceeded the male rate of 78/100 000; suicide was responsible for 49% of all deaths in women and 38% of all deaths in men at these ages. CONCLUSIONS: This is the second largest study to date that has used verbal autopsy to estimate mortality rates in India. Suicides accounted for 9% of total deaths, and the ratio of male to female suicide was 1: 0.72. The overall (male + female) annual suicide rate was 62/100 000 population. The female suicide rate at ages 15-24 years was higher than the male rate in that age-group and other female age-groups. About 50% of suicides were by self-poisoning, one-third by hanging and one-eighth by self-immolation.